Women prolactinemia in height and sea level. - Quintana, Luis (2015)
We studied serum prolactin levels, the prevalence of hyperprolactinemia and galactorrhea, and its correlation with reproductive pathology in two groups of native women in Lima (150 m) and Cerro de Pasco (4340 m). Serum prolactin levels were higher than sea level in height. No differences in prolactin levels between follicular and luteal phase is found. Hiperprolaetinemia prevalence was 2.6 times higher in Lima than in Cerro de Pasco. In Lima the highest prevalence of hyperprolactinemia is seen in cases of polymenorrhea (100%) and oligomenorrhea (68.5%). In height, neither case showed reproductive pathology with hyperprolactinemia. Galactorrea prevalence in cases of reproductive pathology was 76% to 36% in Lima and Cerro de Pasco. Of all cases with 65.4% galactorrhea in Lima and 6.2% in Cerro de Pasco they had concomitant hyperprolactinemia. In conclusion, the prevalence of hyperprolactinemia and galactorrhea is lower in height.